Socio-Economic Impact of End-Stage Renal Disease on the Patients in District Faisalabad Punjab Pakistan - Muhammad Nafees, Madıha Naz, Farwa Batool, Rizwan Ashraf, Muhammad Usman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Chronic Kidney Disease (CKD) is associated with premature deaths, low quality of life, and high-cost medical treatment problems worldwide. When CKD does not cure, the End-Stage Renal Disease (ESRD) emerges which required to be treated by Renal Replacement Therapy (RRT) which comprises of a kidney transplant, or dialysis. Due to the dependency on the family members, inability to participate in economic activities and inability to fulfill various social responsibilities, such patients face many social problems. Objectives: This study focused on problems faced by End-Stage Renal Disease (ESRD) patients, and suggested some policy measures to eliminate the social problems of such patients. Study design: Cross-sectional study. Place and duration: Dialysis center of Allied Hospital Faisalabad, Pakistan, December 2021. Methodology: 105 respondents through a convenient sampling technique were recruited and responses were obtained using a structured interview schedule. Data were analyzed and interpreted using (SPSS version 22). Conclusion: The study concluded that patients of ESRD were facing a lot of social problems due to the inability to participate in paid work, inability to fulfill their social responsibilities, and dependency on their family members for their dialysis and routine activities. There is a need to address their social problems through suitable policy initiatives.